2001
DOI: 10.1161/01.str.32.2.442
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Monitoring of Midline Shift in Space-Occupying Stroke

Abstract: Background and Purpose-Transcranial color-coded duplex sonography (TCCS) allows bedside imaging of intracranial hemodynamics and parenchymal structures. It provides reliable information regarding midline shift (MLS) in space-occupying hemispheric stroke. We studied the value of MLS measurement to predict fatal outcome at different time points after stroke onset. Methods-Forty-two patients with acute, severe hemispheric stroke were enrolled. Cranial computed tomography (CCT) and extracranial duplex sonography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
1
10

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(87 citation statements)
references
References 65 publications
(62 reference statements)
1
75
1
10
Order By: Relevance
“…1 This spaceoccupying effect causes displacement of midline structures and can lead to cerebral herniation and death. 3,4 Mechanical compression of adjacent brain structures further reduces local cerebral blood flow and thus can cause additional ischemic damage. 4 In the present study we evaluated a noninvasive morphometric technique that allows quantification of the spaceoccupying effect of brain edema in a rat stroke model, using T2-weighted MRI.…”
mentioning
confidence: 99%
“…1 This spaceoccupying effect causes displacement of midline structures and can lead to cerebral herniation and death. 3,4 Mechanical compression of adjacent brain structures further reduces local cerebral blood flow and thus can cause additional ischemic damage. 4 In the present study we evaluated a noninvasive morphometric technique that allows quantification of the spaceoccupying effect of brain edema in a rat stroke model, using T2-weighted MRI.…”
mentioning
confidence: 99%
“…Furthermore, monitoring MLS via TCCD safely predicts early mortality and prognosis of conservative clinical treatment of hemispheric ischemic stroke [18] . Unlike ischemic stroke, intracranial hemorrhage MLS is caused by both the volume of hematoma and the formation of edema, which can make outcomes difficult to predict [20] . Patients with FHF who develop brain swelling and IH can benefit from this method, although it has not yet been described in the literature.…”
Section: Transcranial Color-coded Duplex Ultrasonographymentioning
confidence: 99%
“…Gerriets et al demonstrated that TCCS monitoring of midline shift is a useful tool in management of critically ill patients who cannot undergo repeated CT scans. (Gerriets et al, 2001) It must be pointed out that there are no exact radiologic indicative criteria for performing the DC.…”
Section: Indicationsmentioning
confidence: 99%
“…That means that patients with the MCA or MCA and Internal Carotid Artery (ICA) occlusion where early recanalisation has not been carried out and the brain ischemia in the region of the whole territory of the middle cerebral artery developed are potentially threatened by malignant edema. Patients with midline shift more than 4 mm according to transcranial color-coded sonography at 24 hours from stroke onset reached poor outcome (Gerriets et al, 2001). There is no evidence that patients with the dominance of infarction have a poorer favourable outcome than patients with 78 nondominance supratentorial infarction.…”
Section: Outcomementioning
confidence: 99%